2014
DOI: 10.1038/srep07517
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected biotic resilience on the Japanese seafloor caused by the 2011 Tōhoku-Oki tsunami

Abstract: On March 11th, 2011 the Mw 9.0 2011 Tōhoku-Oki earthquake resulted in a tsunami which caused major devastation in coastal areas. Along the Japanese NE coast, tsunami waves reached maximum run-ups of 40 m, and travelled kilometers inland. Whereas devastation was clearly visible on land, underwater impact is much more difficult to assess. Here, we report unexpected results obtained during a research cruise targeting the seafloor off Shimokita (NE Japan), shortly (five months) after the disaster. The geography of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…The occurrence of displaced benthic foraminifera and their interpretation in terms of submarine sediment transport and deposition by backwash waves have already been discussed by many authors who studied the 2004 and 2011 tsunami deposits (Sugawara et al ., ; Jonathan et al ., ; Milker et al ., ; Toyofuku et al ., ), as well as the 1755 historical tsunami deposit off the Algarve coast in Portugal (Quintela et al ., ). Hence, it was observed that in several offshore tsunami layers, displaced foraminifera species along with backwash coarse‐grained sediments are often represented by a significant amount of coastal foraminifera (marine/estuarine species as well as epiphytic taxa) often combined with organic matter enrichment.…”
Section: Discussionmentioning
confidence: 97%
“…The occurrence of displaced benthic foraminifera and their interpretation in terms of submarine sediment transport and deposition by backwash waves have already been discussed by many authors who studied the 2004 and 2011 tsunami deposits (Sugawara et al ., ; Jonathan et al ., ; Milker et al ., ; Toyofuku et al ., ), as well as the 1755 historical tsunami deposit off the Algarve coast in Portugal (Quintela et al ., ). Hence, it was observed that in several offshore tsunami layers, displaced foraminifera species along with backwash coarse‐grained sediments are often represented by a significant amount of coastal foraminifera (marine/estuarine species as well as epiphytic taxa) often combined with organic matter enrichment.…”
Section: Discussionmentioning
confidence: 97%
“…). While previous efforts attempted to use 210 Pb to identify offshore deposits of the 2004 Indian Ocean tsunami (Feldens et al , ; Sakuna et al , ) and Tohoku‐oki tsunami (Toyofuku et al ., ), contamination of caesium released from the accident at the Fukushima‐Daiichi Nuclear Plant can provide solid chronological evidence in Sendai Bay (Ikehara et al , 2014). This paper presents sediment facies observed in cores at 44 sites combined with the measurement of 134 Cs concentration to identify the tsunami deposits, examining their variations and inferred sedimentary processes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the knowledge of the ecological condition after the disaster will be important for encouraging victims to resume their normal life. Toyofuku et al (2014) reported that the biotic resilience in Tohoku area was quicker than they had expected, and it means that there would be active interactions between living organisms and debris. Tsunami debris will stay in nature for a certain time.…”
Section: Discussionmentioning
confidence: 89%